2006
DOI: 10.1007/s11069-005-4656-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Fragility of Building Structures in Taiwan

Abstract: This paper describes procedures of damage assessment for building structures in Taiwan Earthquake Loss Estimation System (TELES), and focuses on evaluation of parameters used in the building damage assessment. The objective of this paper is to define the building classification and provide the fragility functions of the general building structures in Taiwan by using the available data. The organization of this paper is as follows. First, the types of the building structures in Taiwan are reviewed and a classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…They showed that the results of loss estimation are relatively insensitive to the spatial resolution of the building stock for exposure at grid sizes less than 2 km × 2 km. It has been assumed that all cells contain the same number of buildings, which are typical for Taiwan (Liao et al 2006), namely: steel-braced frames of four to seven stories.…”
Section: Analysis Of Damage and Loss Estimationsmentioning
confidence: 99%
See 4 more Smart Citations
“…They showed that the results of loss estimation are relatively insensitive to the spatial resolution of the building stock for exposure at grid sizes less than 2 km × 2 km. It has been assumed that all cells contain the same number of buildings, which are typical for Taiwan (Liao et al 2006), namely: steel-braced frames of four to seven stories.…”
Section: Analysis Of Damage and Loss Estimationsmentioning
confidence: 99%
“…The components of variability related to the seismic demand and the capacity are discussed by Porter et al (2002); Crowley et al (2005); Bommer and Crowley (2006). In our study, we used the PGA-based fragility curves developed by Liao et al (2006). The authors reviewed the types of building structures in Taiwan and proposed the classification to be implemented in the Taiwan Earthquake Loss Estimation System (TELES).…”
Section: Analysis Of Damage and Loss Estimationsmentioning
confidence: 99%
See 3 more Smart Citations